Mitochondria, Estrogen and Female Brain Aging - Lejri, Imane; Grimm, Amandine; Eckert, Anne (Frontiers in Aging Neuroscience, 2018)
Mitochondria play an essential role in the generation of steroid hormones including the female sex hormones. These hormones are, in turn, able to modulate mitochondrial activities. Mitochondria possess crucial roles in cell maintenance, survival and well-being, because they are the main source of energy as well as of reactive oxygen species (ROS) within the cell. The impairment of these important organelles is one of the central features of aging. In women’s health, estrogen plays an important role during adulthood not only in the estrous cycle, but also in the brain via neuroprotective, neurotrophic and antioxidant modes of action. The hypestrogenic state in the peri- as well as in the prolonged postmenopause might increase the vulnerability of elderly women to brain degeneration and age-related pathologies. However, the underlying mechanisms that affect these processes are not well elucidated. Understanding the relationship between estrogen and mitochondria might therefore provide better insights into the female aging process. Thus, in this review, we first describe mitochondrial dysfunction in the aging brain. Second, we discuss the estrogen-dependent actions on the mitochondrial activity, including recent evidence of the estrogen—brain-derived neurotrophic factor and estrogen—sirtuin 3 (SIRT3) pathways, as well as their potential implications during female aging.